TEM assessment of As-doped GaN epitaxial layers grown on sapphire - Fay, Mike W.; Harrison, Ian; Larkins, Eric C.; Novikov, Sergei V.; Foxon, C.T.; Brown, Paul D. (Institute of Physics Publishing, 2004)
TEM investigations of As-doped GaN layers grown by plasma-assisted molecular beam epitaxy on sapphire substrates reveal the presence of extensive regions of cubic stacking disorder within the hexagonal GaN matrix. Electron energy loss spectroscopy suggests the localization of As within grains immediately below domains containing stacking disorder, and additionally at the layer surface. This suggests that localised strain plays a role in the formation mechanism of the stacking faults.